2002
DOI: 10.1002/cne.10095
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of two splice variants of the glutamate transporter GLT1 in the retinas of humans, monkeys, rabbits, rats, cats, and chickens

Abstract: Antibodies have been generated against two carboxyl-terminal splice variants of the glutamate transporter GLT1, namely, the originally described version of GLT1 and GLT1-B, and labelling has been examined in multiple species, including chickens and humans. Although strong specific labelling was observed in each species, divergent patterns of expression were noted. Moreover, each antibody was sensitive to the phosphorylation state of the appropriate protein, because chemical removal of phosphates using alkaline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 17 publications
5
68
0
Order By: Relevance
“…The differential compartmentation of glutamate transporters within very small domains of sperm is comparable to the microcompartmentation of such proteins in the brain and retina. 21,38 Roles of glutamate and possible functional consequences of glutamate transporter expression It has previously been shown that mice which lack EAAC1 in the epididymis (due to the knockout of c-ros) 11 exhibit swollen spermatozoa. 12 This has been interpreted as an example of the role of glutamate as an osmolyte, which in this instance would be dys-regulated due to impaired epididymal supply of the osmolyte (glutamate) or its premature loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differential compartmentation of glutamate transporters within very small domains of sperm is comparable to the microcompartmentation of such proteins in the brain and retina. 21,38 Roles of glutamate and possible functional consequences of glutamate transporter expression It has previously been shown that mice which lack EAAC1 in the epididymis (due to the knockout of c-ros) 11 exhibit swollen spermatozoa. 12 This has been interpreted as an example of the role of glutamate as an osmolyte, which in this instance would be dys-regulated due to impaired epididymal supply of the osmolyte (glutamate) or its premature loss.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34][35][36][37][38] Figure 1 schematically illustrates the locations of antibody epitopes for normally spliced GLAST and the exon-skipping forms of GLAST (GLAST1a and GLAST1b). Multiple GLT1 antisera were used in this study (Figure 2).…”
Section: Primary Antibodies Against Transportersmentioning
confidence: 99%
“…Given the complex mechanisms regulating GLT-1 expression (Anderson and Swanson, 2000;Gegelashvili and Schousboe, 1997;Plachez et al, 2000), its post-transcriptional regulation in neurons was invoked to explain the contrasting data (e.g., Danbolt et al, 1998). It subsequently became apparent that part of the uncertainty was because of the existence of three different isoforms, GLT-1a-c. (Berger et al, 2005;Chen et al, 2002Chen et al, , 2004Pines et al, 1992;Rauen et al, 2004;Reye et al, 2002;Schmitt et al, 2002;Sullivan et al, 2004). Despite regional variations of expression, GLT-1a (the protein originally called GLT-1), appears more abundant and more closely related to synapses than GLT-1b, presumably mediating most of the known synaptic effects of GLT-1 (Berger et al, 2005;Chen et al, 2004;Lauriat and McInnes, 2007;Sullivan et al, 2004); GLT-1c is expressed only in the retina.…”
Section: Introductionmentioning
confidence: 98%
“…In order to maintain normal retinal function, glutamate must be removed rapidly from the synaptic cleft. At the molecular level, five glutamate transporters have been cloned: excitatory amino acid transporters (EAAT) 1-5, all of which have been identified in the retina [13,14,[18][19][20][21][22]. Although the function of specific transporter types is contentious, it is clear that GLAST (EAAT1) is the predominant transporter for removal of glutamate within the retina and defects in its function lead to major deleterious effects on vision [20,23,24].…”
Section: Introductionmentioning
confidence: 99%